2013
DOI: 10.1186/1742-4690-10-41
|View full text |Cite
|
Sign up to set email alerts
|

Cell-associated HIV RNA: a dynamic biomarker of viral persistence

Abstract: In most HIV-infected individuals adherent to modern antiretroviral therapy (ART), plasma viremia stays undetectable by clinical assays and therefore, additional virological markers for monitoring and predicting therapy responses and for measuring the degree of HIV persistence in patients on ART should be identified. For the above purposes, quantitation of cell-associated HIV biomarkers could provide a useful alternative to measurements of viral RNA in plasma. This review concentrates on cell-associated (CA) HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
118
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 166 publications
(189 reference statements)
5
118
0
3
Order By: Relevance
“…This study demonstrated higher levels of multiply spliced HIV RNA transcripts in the cells of study participants with detectable CMV in semen but no difference in unspliced HIV RNA or 2-LTR circles. This discordant HIV RNA expression pattern (i.e., higher levels of multiply spliced than of unspliced HIV RNA) likely represents "blocked early-stage latency" as a form of latently HIVinfected cells (36,37). We also found a trend for CMV shedders to have increased multiply spliced HIV RNA/HIV DNA ratios but no difference in unspliced HIV RNA/HIV DNA ratios.…”
Section: Discussionmentioning
confidence: 62%
“…This study demonstrated higher levels of multiply spliced HIV RNA transcripts in the cells of study participants with detectable CMV in semen but no difference in unspliced HIV RNA or 2-LTR circles. This discordant HIV RNA expression pattern (i.e., higher levels of multiply spliced than of unspliced HIV RNA) likely represents "blocked early-stage latency" as a form of latently HIVinfected cells (36,37). We also found a trend for CMV shedders to have increased multiply spliced HIV RNA/HIV DNA ratios but no difference in unspliced HIV RNA/HIV DNA ratios.…”
Section: Discussionmentioning
confidence: 62%
“…With HIV eradication becoming an emerging goal of HIV medicine, elucidation and monitoring of HIV-1-infected reservoirs is critical (16). To that end, we performed studies aimed to combine analyses of replication-competent HIV-1 reservoirs with the virus already present in plasma to obtain a broader representation of HIV-1 quasispecies.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in HIV transcription have been demonstrated in all trials by showing an increase in the level of cell-associated HIV RNA (CA RNA) in total and resting CD4 ϩ T cells (21). Synthesis of unspliced (US) HIV RNA is the first step in virus transcription, and multiple subsequent steps, including splicing, cytoplasmic export, synthesis of the regulatory proteins tat and rev, maturation, and budding, are subsequently required for virion release (22), but US HIV RNA is a marker that HIV transcription has been initiated (18).…”
mentioning
confidence: 99%